Substrate placement inside CVD tube for graphene production - Osman, Muhammad Naqib; Ani, Mohd Hanafi; Syed Abu Bakar, Syed Noh (Trans Tech Publications Ltd, 2020)
Electronics and energy storage industry demand production of high-quality graphene which currently still a challenge. Chemical vapor deposition (CVD) has shown promises for high- quality graphene production. However, it involves control of many parameters from different aspects such as thermal-fluid, mass transport, and chemical reaction. Thermal fluid aspect plays a significant role in CVD production of graphene but yet to be explored extensively. For a tubular hot-wall CVD with the heating reactor, issue of flow instability that will prolong the existence of vortices and spiral flow until the substrate required attention. Therefore current study aims to find the optimum substrate position inside the furnace. For that purpose the gas flow streamline will be observed, and minimum axial distance of the substrate will be determined. The tubular CVD is modeled using ANSYS Fluent®. The current model will not consider the chemical reaction involves and only single gas is used. This should be enough to seek the influence of thermal-fluid aspects involves in CVD. The CVD tube will be divided into 3 sections where the middle part (furnace) was heated up to 1273K and the other two sections were kept at 300K. Gas was supplied to the tube and the distance from the furnace inlet to the point where the flow is fully developed is measured. Streamlines for the flow is also observed. The streamline shows that there is an induced secondary flow starting at the inlet which lasted until a certain axial distance. For flow with 50 sccm of flowrate needs an axial distance of 5 cm while flow with 250 sccm of flowrate needs 7 cm in order to become a smooth flow. Our results show that the placement of the substrate in the tubular hot- wall CVD required attention in CVD design. For flow with higher flowrate, it requires longer distance for the flow to become smooth and laminar and vice versa.